2019
DOI: 10.17305/bjbms.2019.4500
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention assisted by invasive mechanical ventilation and intra-aortic balloon pump for acute myocardial infarction with cardiogenic shock: Retrospective cohort study and meta-analysis

Abstract: The aim of this study was to compare the mortality outcome in patients with acute myocardial infarction and cardiogenic shock who were treated with percutaneous coronary intervention (PCI) assisted by intra-aortic balloon pump (IABP) + invasive mechanical ventilation (IMV) with historical controls. From January 1, 2016 to June 1, 2017, 60 patients were retrospectively enrolled at Tianjin Chest Hospital. Out of these, 88.3% of patients achieved thrombolysis in myocardial infarction flow 3 after PCI. The all-cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 23 Liu et al found that a lactic acid level of ≥4.5 mmol/L was an independent predictor of death in AMI-cardiogenic shock patients at 1 year. 24 Despite the specificity of such a cut-off being addressed, this finding suggested a sensitive power of lactate in predicting cardiac death with AMI patients during different follow-up periods. However, our results were inconsistent with those previous studies.…”
Section: Discussionmentioning
confidence: 97%
“… 23 Liu et al found that a lactic acid level of ≥4.5 mmol/L was an independent predictor of death in AMI-cardiogenic shock patients at 1 year. 24 Despite the specificity of such a cut-off being addressed, this finding suggested a sensitive power of lactate in predicting cardiac death with AMI patients during different follow-up periods. However, our results were inconsistent with those previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…Another study reports an in-hospital mortality rate of 25% in patients who needed both invasive mechanical ventilation and IABP with PCI, which is comparable to our overall mortality rate, even though not all patients required mechanical ventilator support. The same study reported higher mortality rates of 66% for patients who required PCI with invasive mechanical ventilation and partial IABP [16]. Another study published showed a mortality rate of 37.3% at 30 days and 40.0% at 90 days in patients requiring PCI complicated by cardiogenic shock requiring vasopressors and invasive mechanical ventilation and IABP if needed in the ICU [17].…”
Section: Plos Onementioning
confidence: 89%
“…Prolonged ventilation time was found to be associated with a high SOFA score (7.9 ± 2.2 vs. 5.7 ± 2.4; p<0.001), PCT (4 [IQR: 1-10] vs. 1 [IQR: 0.335-3]; p = 0.001), CRP (10 [IQR: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] vs. 5 [IQR: 2-10]; p = 0.001), positive balance (800 [IQR: 391-1500] vs. 500 [IQR: 300-1000]; p = 0.013), and negative balance (850 [IQR:1500-500] vs. 600 [IQR: 800-500]; p = 0.017), respectively. Vasopressors/Inotropes use (84.2% vs. 44.4%; p<0.001) and duration (48 [IQR: 24-48] hours vs. 24 [IQR 24 -24] hours; p = 0.001) was higher among patients with prolonged ventilation duration, respectively.…”
Section: Risk Assessment and Managementmentioning
confidence: 99%